Lactylation-driven TNFR2 expression in regulatory T cells promotes the progression of malignant pleural effusion - Yao Liu; Qiong Zhou; Siyu Zhang; Wenbei Peng; Haolei Wang; Xuan Xiang; Linlin Ye; Xiaoshan Wei; Zihao Wang; Qianqian Xue (Journal for ImmunoTherapy of Cancer, 2024)
Background Although tumor necrosis factor receptor 2 (TNFR2) has been recognized as an attractive next-generation candidate target for cancer immunotherapy, the factors that regulate the gene expression and their mechanistic effects on tumor-infiltrating regulatory T cells (Treg cells) remain poorly understood.Methods Single-cell RNA sequencing analysis was employed to analyze the phenotypic and functional differences between TNFR2+ Treg cells and TNFR2− Treg cells. Malignant pleural effusion (MPE) from humans and mouse was used to investigate the potential mechanisms by which lactate regulates TNFR2 expression.Results Treg cells with high TNFR2 expression exhibited elevated levels of immune checkpoint molecules. Additionally, the high expression of TNFR2 on Treg cells was positively correlated with a poor prognosis in MPE patients. Moreover, we revealed that lactate upregulated TNFR2 expression on Treg cells, thereby enhancing their immunosuppressive function in MPE. Mechanistically, lactate modulated the gene transcription of transcription factor nuclear factor-κB p65 (NF-κB p65) through histone H3K18 lactylation (H3K18la), subsequently upregulating the gene expression of TNFR2 and expediting the progression of MPE. Notably, lactate metabolism blockade combined with immune checkpoint blockade (ICB) therapy effectively enhanced the efficacy of ICB therapy, prolonged the survival time of MPE mice, and improved immunosuppression in the microenvironment of MPE.Conclusions The study explains the mechanism that regulates TNFR2 expression on Treg cells and its function in MPE progression, providing novel insights into the epigenetic regulation of tumor development and metabolic strategies for MPE treatment by targeting lactate metabolism in Treg cells.